Gap Junction Coding Innexin in Lymnaea stagnalis: Sequence Analysis and Characterization in Tissues and the Central Nervous System - Mersman, Brittany A.; Jolly, Sonia N.; Lin, Zhenguo; Xu, Fenglian (Frontiers in Synaptic Neuroscience, 2020)
Connections between neurons called synapses are the key components underlying all nervous system functions of animals and humans. However, important genetic information on the formation and plasticity of one type, the electrical (gap junction-mediated) synapse, is understudied in many invertebrates. In the present study, we set forth to identify and characterize the gap junction-encoding gene innexin in the central nervous system (CNS) of the mollusc pond snail Lymnaea stagnalis (L. stagnalis). With PCR, 3’ and 5’ RACE, and BLAST searches, we identified eight innexin genes in the L. stagnalis genome, named Lst Inx1-8. Phylogenetic analysis revealed that the L. stagnalis innexin genes originated from a single copy in the common ancestor of molluscan species by multiple gene duplication events and have been maintained in L. stagnalis since they were generated. The paralogous innexin genes demonstrate distinct expression patterns among tissues. In addition, one paralog, Lst Inx1, exhibits heterogeneity in cells and ganglia, suggesting the occurrence of functional diversification after gene duplication. These results introduce possibilities to study an intriguing potential relationship between innexin paralog expression and cell-specific functional outputs such as heterogenic ability to form channels and exhibit synapse plasticity. The L. stagnalis CNS contains large neurons and functionally defined networks for behaviors; with the introduction of L. stagnalis in the gap junction gene field, we are providing novel opportunities to combine genetic research with direct investigations of functional outcomes at the cellular, synaptic, and behavioral levels.